Dutch and Flemish language, culture, and identity in North America - Hietpas, Rachyl; Vanhecke, Charlotte (Bergen Language and Linguistics Studies, 2022)
Modeled after Moquin and Wolf’s (2020) survey on North American Icelandic, this study adds to a growing body of work examining the relationship between language use and cultural identity in postvernacular communities (e.g., Moquin & Wolf 2020, Brown & Hietpas 2019). Through 635 responses to an online survey collected as of February 2022, we present initial quantitative and qualitative findings on the relationship between language and culture among Dutch/Flemish immigrants to North America and their descendants. Our results show that strong Dutch cultural identification among a portion of this group does not necessarily correlate with Dutch language proficiency, especially after the first and second generation. The study further finds that respondents find the maintenance of Dutch language and culture only moderately important, although with slightly higher scores for culture and traditions shown in responses referencing Dutch holiday traditions and foods. These views, which come from arguably some of the most engaged members of these communities as respondents to this optional survey, bear important consequences for the future of Dutch in North America. However, initial analysis suggests that Dutch hotspots, especially those which latch onto “Dutchness” for festivals and tourism purposes, experience more successful maintenance. While the number of responses collected here helps to expand our understanding of the roles of language and cultural identity in heritage communities, future research into these “hotspots” and contrasting them with isolated responses will provide further insight into how the community itself shapes these identities.